Influence of social and demographic factors on clinical status and severity of chronic fatigue syndrome in patients with multiple sclerosis - Sowa, Karolina; Glista, Joanna; Pop, Teresa; Gdańska, Natalia; Adamczyk, Marzena; Adamek, Jolanta (Polish Journal of Public Health, 2012)
Introduction. Chronic fatigue syndrome (CFS) is cha-racterized by apathy, indifference, exhaustion, and lack of energy, and these symptoms are not the result of intense physical or mental work. Chronic fatigue syndrome often accompanies patients with multiple sclerosis (MS).Aim. The aim of this study was to assess the impact of social and demographic factors on clinical status and level of chronic fatigue syndrome in patients with MS.Material and methods. The study group comprised 33 MS patients who were treated at the Department of Rehabilitation and Department of Neurology with the Stroke Treatment Unit from November 20, 2010 to 27 April 2011. The research applied a questionnaire containing social and demographic data and the Barthel Scale, Beck’s Depression Inventory (BDI), the Kurtzke Scale and the Fatigue Severity Scale. The results were analyzed statistically using descriptive statistics and Spearman’s rank correlation coefficient.Results. Statistically significant correlations were confirmed between functional status assessed in the Barthel scale and subjects’ age, disease duration, and the results in the Kurtzke Scale. No statistically significant relationship between the BDI and the analyzed factors was obtained. Significant statistical correlation was obtained between the scores obtained in the Fatigue Severity Scale and family status in the study group. There was also found a weak correlation between the results in the Barthel Scale and Beck Depression Inventory and scores in the Fatigue Severity Scale.Conclusions. A significant statistical correlation was confirmed between the results on Fatigue Severity Scale and family status, occurring depression and functional capacity in carrying out activities of daily living. There was no statistically significant correlation between such factors as gender, place of residence, education, faith, disease duration and prevalence of chronic fatigue syndrome in patients with MS.